Data Science Project I and Data Science Project II Presentation Day - Wan Nur Syahidah, Wan Yusoff (2023)
On 1st – 2nd February 2023, there are 60 students from the programme of Bachelor of Applied Science in Data Analytics with Honours who have been successfully presented their Data Science Project I.